Translating Al-Hikam Aphorisms: Evaluating Unmarked Topical Themes through Theme-Rheme Structure Analysis - Anis, Muhammad Yunus; Arifuddin, Arifuddin; Khabibi Muhammad Luthfi; Reza Sukma Nugraha; Afnan Arummi; Eva Farhah; Tri Yanti Nurul Hidayati (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
Aphorisms are unique literary works known for their memorability, concision, and ambiguity. They have an information structure divided into theme (known information) and rheme (new information), with the